Productivity and quality improvements, revenue increment, and rejection cost reduction in the manual component insertion lines through the application of ergonomics - Yeow, Paul H.P.; Nath Sen, Rabindra (2006)
The study is aimed at improving productivity and quality, increasing revenue and reducing rejection cost of the manual component insertion (MCI) lines in a printed circuit assembly (PCA) factory. Subjective assessment (through questionnaire), direct observation method, and archival data were used. Live experiments were conducted on production lines. Eleven problems were identified, i.e., long search for materials from the stores, unproductive manual component counting, obstructions during insertions, component fall-off while the PCA board was traveling on a U-shaped conveyor, etc. Interventions were made to rectify the problems, i.e., to have only one central store to eliminate confusion of the materials' whereabouts, use weighing scale for component counting, modify the MCI sequence and the bin arrangements to avoid obstructions, and use straight conveyor to reduce handling. As a result, there was a tremendous increase in productivity and yearly revenue (US$4,223,736) and a huge reduction in defects and yearly rejection costs (US$956,136).